Effects of CaTiO3 addition on the microwave dielectric properties and antenna properties of BiVO4 ceramics. (15th October 2019) - Oliveira, R.G.M.; Silva, R.A.; de Morais, J.E.V.; Batista, G.S.; Silva, M.A.S.; Goes, J.C.; de Andrade, H.D.; Queiroz Júnior, I.S.; Singh, C.; Sombra, A.S.B.
Abstract: This paper investigated the microwave dielectric properties through the Hakki-Coleman method of BiVO4 ceramic matrix, obtained by the solid-state reaction method, using 8, 16, 24 and 32 wt% of CaTiO3 . The X-ray diffraction (XRD) was used for the structural characterisation of the crystalline phases present in ceramic before the sinterisation process. The thermal-stability in microwave range was measured in all dielectric samples, and the temperature coefficient of resonant frequency ( τ f ) was found varying from −244.03 ppm °C −1 to −2.7 ppm °C −1 . The CaTiO3 addition reduced the value of the dielectric permittivity ( ε ') close to 25% of the BiVO4 values, keeping the dielectric loss ( tan δ ) around 10 −3 . The experimental and numerical simulated values of the dielectric resonator antenna (DRA) results show the agreement of the input impedance, return loss, bandwidth and radiation patterns. Moreover, all antennae features realised gain above 5dBi. In antenna results, the CaTiO3 addition increased the bandwidth, compared to BiVO4 DRA, that presented bandwidth around 34 MHz.